Fluorescence Biomodulation for Canine Interdigital Furunculosis: Updates for Once-Weekly Schedule - Marchegiani, Andrea; Fruganti, Alessandro; Gavazza, Alessandra; Spaterna, Andrea; Cerquetella, Matteo (Frontiers in Veterinary Science, 2022)
Interdigital furunculosis is a common multifactorial, inflammatory disease of the canine interdigital skin in which lesions commonly become secondarily infected. Fluorescence biomodulation (FBM) administered twice weekly has shown to effectively control clinical manifestation as adjunct therapy to systemic antibiotic use. Since twice weekly regimen could be unaffordable for some pet owners, the aim of this study was to evaluate the effect of once weekly application of FBM in combination with systemic antibiotic on clinical manifestations of canine interdigital pyoderma, comparing the results to those present in literature. Twelve dogs diagnosed with interdigital pyoderma received antibiotic plus once weekly FBM application. Dogs were scored until complete healing on the basis of global lesion score and neutrophil engulfing bacterial score. The results obtained demonstrated that once weekly application of FBM exerts the beneficial effect on interdigital furunculosis healing as per twice weekly. These results indicate that the once weekly application regimen is well tolerated and is yielding similar results to twice weekly applications.